Apatite precipitation on a novel fast-setting calcium silicate cement containing fluoride - Bahram Ranjkesh; Jacques Chevallier; Hamideh Salehi; Frédéric Cuisinier; Flemming Isidor; Henrik Løvschall (Acta Biomaterialia Odontologica Scandinavica)
Aim: Calcium silicate cements are widely used in endodontics. Novel fast-setting calcium silicate cement with fluoride (Protooth) has been developed for potential applications in teeth crowns including cavity lining and cementation. Objective: To evaluate the surface apatite-forming ability of Protooth compositions as a function of fluoride content and immersion time in phosphate-buffered saline (PBS). Material and methods: Three cement compositions were tested: Protooth (3.5% fluoride and 10% radiocontrast), ultrafast Protooth (3.5% fluoride and 20% radiocontrast), and high fluoride Protooth (15% fluoride and 25% radiocontrast). Powders were cap-mixed with liquid, filled to the molds and immersed in PBS. Scanning electron microscopy, energy dispersive X-ray analysis, and Raman spectroscopy were used to characterize the precipitations morphology and composition after 1, 7, 28, and 56 days. Apatite/belite Raman peak height indicated the apatite thickness. Results: Spherical calcium phosphate precipitations with acicular crystallites were formed after 1-day immersion in PBS and Raman spectra disclosed the phosphate band at 965 cm−1, supporting the apatite formation over Protooth compositions. The apatite deposition continued and more voluminous precipitations were observed after 56 days over the surface of all cements. Raman bands suggested the formation of β-type carbonated apatite over Protooth compositions. High fluoride Protooth showed the most compact deposition with significantly higher apatite/belite ratio compared to Protooth and ultrafast Protooth after 28 and 56 days. Conclusions: Calcium phosphate precipitations (apatite) were formed over Protooth compositions after immersion in PBS with increasing apatite formation as a function of time. High fluoride Protooth exhibited thicker apatite deposition.